Liquid urea-formaldehyde slow release fertilizer reduced the frequency of fertigation and increased the yield of spinach (Spinacia oleracea L.). (14th December 2021) - Yang, Guiting; Zhao, Hongmeng; Zhang, Min; Dongdong, Cheng; Chen, Jianqiu; Ma, Jinzhao; Liu, Zhiguang
Abstract: At present, excessive fertilization in vegetable production not only leads to the decline of vegetable quality and yield, but also causes environmental pollution. In this study, a liquid urea-formaldehyde slow release fertilizer (LUFF) was synthesized by using formaldehyde, urea and diammonium hydrogen phosphate. The effects of LUFF on yield, quality, root growth, antioxidant enzyme activity and nutrient absorption of spinach were studied in a pot experiment. Five treatments with four replicates each were established as follows: (1) Control, no fertilizer; (2) CWSF1, conventional water-soluble fertilizer; (3) CWSF2, conventional water-soluble fertilizer reduced by 25%; (4) LUFF1, liquid urea-formaldehyde slow release fertilizer; (5) LUFF2, liquid urea-formaldehyde slow release fertilizer reduced by 25%. Normal N-P2 O5 -K2 O application rate of 2.83-2.73-3.94 g/pot and 25% reduction N-P2 O5 -K2 O of rate (2.12-2.05-2.96 g/pot) were set up. The fertilizer was applied five times-split for CWSF while the equivalent rates of LUFF used as twice-split fertigation. The results showed that the yield of LUFF treatments was significantly increased by 31.81%-77.31% compared with CWSF. Root indexes, such as root length, root projection area and root surface area, were significantly improved by LUFF treatments compared with CWSF. The vitamin C (Vc) concentration and superoxide dismutase (SOD) activity of spinach in LUFF were significantly increased by 7.34%-30.07% and 23.83%-42.52% compared with CWSF. It can be observed from the above results, the LUFF could increase the yield of spinach, improve the quality of spinach, while reducing the frequency of fertigation. Therefore, LUFF may have high application value in agriculture.